The Role of Educators in Cultivating Self-Efficacy Among School-Leaver Enabling Students: Perspectives and Practices - Larsen, Ana; James, Trixie; Robinson, Amy; Jones, Angela; Coleman, Matilda; Lambrinidis, George; Daniel, Rachel (Journal of University Teaching and Learning Practice, 2025)
In Australia, government-funded Enabling programs provide equitable pathways to higher education for students from diverse backgrounds, including increasing numbers of recent school-leavers. This collaborative autoethnographic study explores six Enabling educators’ lived experiences across five universities to understand how they perceive and cultivate self-efficacy among school-leaver students. Thematic analysis revealed three overarching areas: educators’ perceptions of students’ readiness for higher education, strategies used to develop self-efficacy, and barriers that constrain this work. Findings highlight the complexity of fostering self-efficacy in younger cohorts, who often display both overconfidence and low academic self-belief. Educators identified the importance of pedagogies of care, growth mindset, scaffolded mastery experiences, and supportive learning communities. However, their efforts are challenged by limited time, high workloads, and significant emotional labour. The study underscores the need for institutional recognition, professional development, and systemic support to sustain educators’ capacity to build student self-efficacy within Enabling education.